At Westonci.ca, we connect you with the best answers from a community of experienced and knowledgeable individuals. Connect with a community of experts ready to provide precise solutions to your questions quickly and accurately. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.

MaryJo decided to solve the equation 3x - 2 = -x - 6


Sagot :

BRVR
3x-2=-x-6

do the inverse and add 2 to the whole number on the other side which is -6

3x=-x-4

do the inverse with the variable -x and add x to 3x

4x=-4

divide -4/4 since the inverse of multiplication is division

x=-1
Ryan2
 3x - 2 = -x - 6
 3x + x = -6 + 2
 4x = -4
   x = -1